GLOSA BÍBLICA Y CRÍTICA DE TEXTO EN LA EPÍSTOLA AL CARDENAL CISNEROS DE ANTONIO DE NEBRIJA (Analele Universităţii Bucureşti. Limbi şi Literaturi Străine, 2025)
With this paper we aim to present a case study revealing the history and vicissitudes of medieval biblical hermeneutics in the  pragmatic mirror of the humanist and anti-scholastic textual criticism of the early sixteenth century. Taking his cue from the Italian school of Lorenzo Valla, Elio Antonio de Nebrija (1444-1522) applied the rigour of the philological discipline to the practice of critical analysis related to manuscript sources of the biblical text, in order to restore the semantic and functional autonomy of the text against the erroneous variants traditionaly based on an appeal to authority. The letter to Cardinal Cisneros, coordinator of the Polyglot Bible Project and a leading figure of Spanish humanism, highlights the framework of a translatological theory and apoetics of interlingual transfer at the origin of some of the most substantial contributions of Spanish humanism to the comparative study of the Bible in the sixteenth century.
Keywords: Antonio de Nebrija; Biblia Políglota; glosa bíblica; crítica textual; teoría de la traducción